Dexmedetomidine versus Propofol Sedation Reduces Delirium after Cardiac Surgery: A Randomized Controlled Trial. (February 2016) - Djaiani, George; Silverton, Natalie; Fedorko, Ludwik; Carroll, Jo; Styra, Rima; Rao, Vivek; Katznelson, Rita
Abstract : Background: Postoperative delirium (POD) is a serious complication after cardiac surgery. Use of dexmedetomidine to prevent delirium is controversial. The authors hypothesized that dexmedetomidine sedation after cardiac surgery would reduce the incidence of POD. Methods: After institutional ethics review board approval, and informed consent, a single-blinded, prospective, randomized controlled trial was conducted in patients 60 yr or older undergoing cardiac surgery. Patients with a history of serious mental illness, delirium, and severe dementia were excluded. Upon admission to intensive care unit (ICU), patients received either dexmedetomidine (0.4 μg/kg bolus followed by 0.2 to 0.7 μg kg −1 h −1 infusion) or propofol (25 to 50 μg kg −1 min −1 infusion) according to a computer-generated randomization code in blocks of four. Assessment of delirium was performed with confusion assessment method for ICU or confusion assessment method after discharge from ICU at 12-h intervals during the 5 postoperative days. Primary outcome was the incidence of POD. Results: POD was present in 16 of 91 (17.5%) and 29 of 92 (31.5%) patients in dexmedetomidine and propofol groups, respectively (odds ratio, 0.46; 95% CI, 0.23 to 0.92; P = 0.028). Median onset of POD was on postoperative day 2 (1 to 4 days) versus 1 (1 to 4 days), P = 0.027, and duration of POD 2 days (1 to 4 days) versus 3 days (1 to 5 days), P = 0.04, in dexmedetomidine and propofol groups, respectively. Conclusions: When compared with propofol, dexmedetomidine sedation reduced incidence, delayed onset, and shortened duration of POD in elderly patients after cardiac surgery. The absolute risk reduction for POD was 14%, with a number needed to treat of 7.1. Abstract : When compared with propofol, dexmedetomidine sedation reduced incidence, delayed onset, and shortened duration of postoperative delirium in elderly patients after cardiac surgery.